Podcast dedicado a la temática de la lucha libre profesional: caso Luchamaniacs el podcast - Lau Bardi, Luis Andrés (2020)
Luchamaniacs the Podcast is a proyect derivative from the Peruvian fanpage “Luchamaniacs” that was born with the goal to obtain a closer approach with the fans from this type of sports enterteiment in different platforms starting with radio programs as Spotify. The porpuse of this report is to inform why we choose to start with this podcast format to gain a better approach with our followers also the results and learned lessons in this process.